2021
DOI: 10.20945/2359-3997000000403
|View full text |Cite
|
Sign up to set email alerts
|

Searching chromosome mosaicisms in 45,X Turner syndrome: how relevant is it?

Abstract: Objective: To investigate the presence of chromosome mosaicism, especially for the presence of Y derived material in 45,X women with Turner syndrome (TS). Materials and methods: FISH and PCR were performed for the presence of chromosome mosaicism and Y-derived-material and genetic findings were correlated to clinical data. Results: Thirty-one participants were enrolled: 18 (58%) had chromosome mosaicisms (FISH), Y-derived material was found in 2. Yet, SRY primer was found with PCR in only one of them and DYZ3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We expected that a substantial of X monosomy cases would be reclassified to the "low-frequency" 45,X/46,XX mosaic form by using the FISH method. Our expectation was driven by the findings of previous studies that investigated the role of FISH form buccal smear and proposed that tissue-specific karyotyping may explain the discrepancies between karyotypes and phenotypes of individuals with TS [17,18]. However, the FISH of the cells originating from the three distinct germ layers verified X monosomy in the majority of our patients.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We expected that a substantial of X monosomy cases would be reclassified to the "low-frequency" 45,X/46,XX mosaic form by using the FISH method. Our expectation was driven by the findings of previous studies that investigated the role of FISH form buccal smear and proposed that tissue-specific karyotyping may explain the discrepancies between karyotypes and phenotypes of individuals with TS [17,18]. However, the FISH of the cells originating from the three distinct germ layers verified X monosomy in the majority of our patients.…”
Section: Discussionmentioning
confidence: 53%
“…However, this was not confirmed by another recent analysis [15]. In addition, studies that explored the tissue-specific mosaicism revealed substantial karyotype differences and indicated that the use of FISH analyses of buccal smears could potentially help to clarify the phenotypic variability in TS [16-18]. Considering the mechanism by which somatic mosaicism emerges [19], it cannot also be excluded that the phenotype of individuals with TS depends on whether the loss of the X chromosome occurred before or after the formation of all three germ layers.…”
Section: Introductionmentioning
confidence: 99%